Dietary Patterns and Anemia Status Among Third Trimester Pregnant Women in the working area of Sandaran Public Health Center in 2025 - Subaidah S; Hestri Norhapifah; Risnawati; Sucita Tripertiwi (Poltekkes Kemenkes Kupang, 2026)
Background: Anemia in pregnant women remains a public health problem with a high prevalence in Indonesia and contributes to an increased risk of preterm delivery, low birth weight, as well as maternal and infant morbidity and mortality. This condition is generally caused by iron deficiency, which is closely related to dietary patterns, particularly during the third trimester when nutritional requirements increase, making unbalanced dietary intake more likely to increase the risk of anemia. Objectives: This study aimed to analyze the relationship between dietary patterns and anemia status among third-trimester pregnant women in the working area of Puskesmas Sandaran in 2025. Methods: This study employed an analytic observational design with a cross-sectional approach. The population consisted of all third-trimester pregnant women who attended antenatal care at the study site, with a sample of 32 third-trimester pregnant women selected using an accidental sampling technique. Data were collected through a dietary pattern questionnaire and hemoglobin level examination obtained from the Maternal and Child Health (MCH) handbook. The data were analyzed using univariate and bivariate analysis with Fisher’s Exact Test (α=5%) and Risk Estimate analysis. Results: The results showed that most respondents had good dietary patterns (78.1%) and were not anemic (56.3%). There was a significant relationship between dietary patterns and anemia status (p=0.001). Pregnant women with good dietary patterns had a lower risk of developing anemia (RE=0.280; 95% CI: 0.149–0.525). Conclusions: Dietary patterns are significantly associated with anemia status among pregnant women, especially during the second and third trimesters when iron requirements increase and physiological hemodilution occurs due to a greater increase in plasma volume compared to erythrocyte mass. This condition causes hemoglobin levels to decrease, making pregnant women more susceptible to anemia if nutritional intake is not adequately fulfilled. Therefore, improving dietary patterns from the early stages of pregnancy through the consumption of balanced nutritious foods rich in iron, protein, folic acid, vitamin B12, and vitamin C is an important effort in preventing anemia among pregnant women.